Diversity Development in Postsocialist Cities: The Example of East Germany. Issue 2 (3rd April 2021) - Glorius, Birgit
Abstract: When comparing integration patterns, policies, and attitudes towards migration, postsocialist European countries stand out from West European countries in having a less-developed integration infrastructure, fewer immigrants and less openness towards migration and diversity. Focusing on the case of East Germany, this article highlights the specifics of a migration and integration environment that was shaped by the post-socialist transformation experiences. Taking on a relational geography perspective, it shows a strong path dependence of diversity development in postsocialist societies. The analysis of public debates and opinions reveals a discursive framing of "migration" embedded into Western-Eastern power geometries, which also explains the positions towards integration and diversity. Hence, local manifestations of postsocialist transformation societies with their varying degrees of tolerance, openness, or rejection can only be understood if the hegemonic relationship between East and West is taken into account.